Speed fluctuation during a 10 km run affects subjective exertion and blood lactate levels of world-class athletes - Takii, Y.; Sumi, D.; Matsunaga, R.; Ko, Y.; Marcora, S.; Taniguchi, N.; Sakaguchi, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In long-distance time trials, a constant pace strategy is considered the fastest [1]. However, elite marathon runners fluctuate their speed during the race [2]. The effects of such speed fluctuations on the physical and mental states of the athletes remain unclear. The purpose of this study was to determine the effect of speed fluctuation during a race-simulated 10 km run on the biomechanics, physiology and psychology of world-class distance runners. METHODS: Nineteen elite male and female athletes, who have ever been ranked 1-175th in the highest positions of World Athletics Rankings for either road running, marathon, cross-country, or 1500m, participated in this study. They were divided into four groups based on sex and the latest available seasonal best. A circuit course was set up in Plaza de America, Seville, Spain. In the constant (CON) condition, the athletes ran 10 km at a speed set for each group, which was calculated as 90% of the average speed of their seasonal best times within each group. In the fluctuating (FLU) condition, they ran 10 km at speeds fluctuated ±11-12% around the average speed. Blood lactate levels and the height of counter movement jump (CMJ) were evaluated before and after the run and calculated as percentage changes. Heart rate (HR), cadence and step length were measured during the run and averaged during 8-15 of 16 laps. The ratings of perceived exertion (RPE) were measured at the end of laps 4, 8, 12, and 16 using Borg`s CR10 scale. The session RPE was obtained right after the 10 km run. RESULTS: The mean speeds for each group were 5.48±0.03, 5.30±0.07, 4.95±0.06, and 4.62±0.07 m/s in the CON condition and 5.47±0.17, 5.27±0.11, 4.94±0.06, and 4.58±0.04 m/s in the FLU condition. The completion time was 33:21±2:11 and 33:30±2:09 for the CON and FLU conditions, respectively, with the latter being significantly longer (P < 0.001). Blood lactate levels showed no significant changes before and after the run under CON conditions but increased significantly under FLU conditions (P < 0.001). The post-run blood lactate level was significantly higher in the FLU condition than in the CON condition (FLU: 2.6 ± 1.3 mmol/L, CON: 1.5 ± 0.7 mmol/L, P < 0.001). There were no significant differences in percentage change of CMJ (FLU: 104.8 ± 12.2 %, CON: 104.8 ± 11.0 %), HR (FLU: 160.5 ± 10.0 bpm, CON: 162.0 ± 7.1 bpm), cadence (FLU: 182.8 ± 6.9 bpm, CON: 183.4 ± 6.7 bpm) or step length (FLU: 1.65 ± 0.12 m, CON: 1.65 ± 0.12 m) between the two conditions. The RPE score showed no significant changes during the CON condition but increased significantly from lap 4 to 16 in the FLU condition (P = 0.019). The session RPE score was significantly higher in the FLU condition than in the CON condition (FLU: 3.4 ± 0.6, CON: 2.9 ± 0.7, P = 0.002). CONCLUSION: Speed fluctuations during a 10 km run do not change the average HR and running mechanics, while increasing world-class athletes subjective exertion and blood lactate levels.